IMPACT OF THE HBM PSYCHOTHERAPEUTIC MODEL ON ANXIETY DISORDER: A CASE STUDY - Certal, Catarina; Medeiros, Milene (Advances in Social Sciences Research Journal, 2021)
Generalized anxiety disorder (GAD) is characterized by excessive worrying and/or fear in everyday contexts, for at least 6 months (APA, 2014). The study participant is female, 41 years old and she has severe anxiety symptoms. We used as a method a psychodiagnosis with a clinical interview, following the assessment protocol of the Human Behavior Map Model (HBM), the Beck Anxiety Inventory (BAI), the Pittsburgh Sleep Quality Index and the Beck Depression Inventory - Second Edition (BDI-II). The theoretical framework adopted was the HBM Psychotherapeutic Model, in which the intervention was anchored on the human behavior map. This map describes the conscious and unconscious processes of the human mind. HBM has two techniques to release emotional states: athenese and morfese (Certal et al., 2016). This intervention led to the improvement of the studied variables in the participant, particularly the reduction of the GAD symptoms.